Integrating The Topic Of Audiovisual Translation Into The Curriculum For Translation Education In Indonesia - Niken Paramita; Anizar Ahmad Yasmin (Pascasarjana UM, 2017)
Abstract: This paper aims to find out what actually the industry needs from their translators when performing Audiovisual (AV) translation, and whether the academic environment, in this case the English Department of Universitas Brawijaya Malang, has fulfilled the industrial needs. From the re-sults of academic document observation and questionnaire to owners of an Indonesian localization company, the authors make some recommendations to include the topic of AV translation in the course of translation that is currently available in the aforementioned English Department. The topic is comprised of the basic concepts of AV text and AV translation, practice of dubbing script translation, and practice of subtitling. The modification of the available course is expected to make the course more relevant to the current needs.Key Words: audiovisual translation, curriculum, instructional materials, translation course, translation pedagogyAbstrak: Penelitian ini bertujuan untuk mengetahui kebutuhan industri penerjemahan dalam penerjemah-an AV serta melihat apakah lingkungan akademiknya, dalam penelitian ini adalah Jurusan Sastra Inggris Universitas Brawijaya Malang, telah memenuhi kebutuhan industri penerjemahan. Hasil observasi do-kumen akademik dan kuisioner yang diberikan kepada pemilik industri penerjemahan dan pelokalan di Indonesia, maka topik terjemahan AV dapat dimasukkan dalam mata kuliah terjemahan pada Jurusan Sastra Inggris Universitas Brawijaya Malang. Topik terjemahan AV terdiri dari konsep dasar teks AV dan terjemahan teks AV, praktik terjemahan naskah penyuaraan atau dubbing, dan praktik subtitling. Modifikasi pada mata kuliah terjemahan yang tersedia diharapkan dapat memenuhi kebutuhan industri terjemahan saat ini. Kata kunci: terjemahan audiovisual, kurikulum, materi instruksional, mata kuliah terjemahan, pendidikan terjemahan